Systematics of the Common Kingsnake (Lampropeltis getula; Serpentes: Colubridae) and the burden of heritage in taxonomy - Pyron, R. Alexander; Burbrink, Frank T. (Zootaxa, 2009)
We present a systematic revision of the Lampropeltis getula group, based on a recent range-wide phylogeographic analysis. We define our theoretical and operational concepts of species delimitation, and provide diagnoses based on mitochondrial DNA evidence, ecological niche modeling, morphology, and historical precedence. We find support for the recognition of five distinct species, which bear the name of the nominate subspecies found primarily within the range of each phylogeographic lineage: the Eastern lineage (Lampropeltis getula, Eastern Kingsnake), the Mississippi lineage (L. nigra, Black Kingsnake), the Central lineage (L. holbrooki, Speckled Kingsnake), the Desert lineage (L. splendida, Desert Kingsnake), and the Western lineage (L. californiae, California Kingsnake). Interestingly, all of these taxa had originally been described as distinct species and recognized as such for up to 101 years (in the case of L. californiae) before being demoted to subspecies. We discuss the impact that increasingly detailed genetic information from phylogeographic analyses may have on traditional taxonomy.